Molecular ordering of A(D–A′–D)2-based organic semiconductors through hydrogen bonding after simple cleavage of tert-butyloxycarbonyl protecting groups. (23rd January 2018) - Trinh, Cuc Kim; Lee, Hong-Joon; Choi, Jin Woo; Shaker, Mohamed; Kim, Wonbin; Lee, Jae-Suk
Abstract : Molecular ordering of organic semiconductors comprising a newly designed A(D–A′–D)2 system was achieved through hydrogen bonding after removal of tert -butyloxycarbonyl substituents. Abstract : We have successfully achieved the molecular ordering of semiconducting small molecules comprising a newly designed A(D–A′–D)2 system. The A(D–A′–D)2 small molecules have two different acceptors based on isoindigo and diketopyrrolopyrrole along with tert -butoxycarbonyl ( t -Boc) groups and hexyl chains, which improve the solubility of the materials. After simple thermal annealing, the t -Boc groups were removed to allow strong hydrogen bonds between N–H⋯CO to form, and this resulted in improved molecular ordering of the organic semiconductors. The crystalline morphology was confirmed by X-ray diffraction coupled with high-voltage electron microscopy, and the resulting materials showed improved hole mobilities. In this work, the effect of the incorporation of t -Boc groups onto A(D–A′–D)2 -based organic semiconductors on their morphological and electrical properties was evaluated.